Fikih Inklusif Dalam Konteks Multikulturalisme Sosial Keagamaan Masyarakat Indonesia (Studi Pemikiran KH. Abdul Qodir AF) - Nilna Fauza (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2018)
As a discourse that is often considered hegemonic in Islamic studies, Fiqh often contributes to the emergence of various perspectives, including exclusive perspectives. As a matter of fact, Fiqh which once offered an abundance of thoughts and perspectives is now often used as a tool of truth legitimacy (truth claim). That means the truth (piety) of a person is often attributed to how pious s/he is in applying Islamic laws. Furthermore, Fiqh which was initially nothing but merely a person's understanding of God's will, is often positioned as an ideology of which others must obey its truth. On the basis of this ideologization, certain understanding often legitimizes itself as the only understanding to generalize a truth or reality. Meanwhile, other understandings are considered to have no authority. Therefore, they must be rejected even though establishing only one religious understanding in the midst of a multicultural society like in Indonesia, is very prone to cause conflicts. Considering the case previously mentioned, establishing Fiqh from a figure who is inclusive and sensitive to multiculturalism becomes important for Muslims in Indonesia in order to have a variety of perspectives in social life and to be able to show the public that Islamic laws can be a social integration instead of a trigger for social disintegration.